2009
DOI: 10.1123/jsep.31.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Sport Performance: An Exploration of Happiness, Hope, and Anger

Abstract: We conducted three experiments to examine the relationships between emotions and subcomponents of performance. Experiment 1 revealed that anger was associated with enhanced gross muscular peak force performance but that happiness did not influence grammatical reasoning performance. Following Lazarus (1991, 2000a), we examined hope rather than happiness in Experiment 2. As hypothesized, hope yielded faster soccer-related reaction times in soccer players. Experiment 3 was an examination of extraversion as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
101
4
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 58 publications
(95 reference statements)
15
101
4
14
Order By: Relevance
“…Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009). In conclusion, wexposure to emotional images impacts the accuracy but not variability of a sustained low-level force contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is no evidence that pairing emotion and motor processes alters the typical pattern of emotional reactivity demonstrated when passively viewing emotional images (Coombes, Janelle, & Duley, 2005;Schmidt et at., 2009). Future research efforts are needed to (a) qualify these findings in healthy and clinical samples across the lifespan (Christou et al, 2004), (b) investigate the cortical and subcortical neural circuits that underlie the interaction between emotion and movement (Borsook, 2007;Coombes, Tandonnet et al, 2009;Hajcak et al, 2007;Pessiglione et al, 2007;Schmidt et al, 2009;van Loon et al, 2010), and (c) examine the implications of emotion-induced changes in movement in a variety of performance settings (Woodman et al, 2009). In conclusion, wexposure to emotional images impacts the accuracy but not variability of a sustained low-level force contraction.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that hope predicted athletic outcomes in female cross-country and track athletes, and considered this emotion to be essential success in sports. In addition, more recently, in an investigation with 18 semiprofessional male British soccer players, Woodman et al (63) found that hope generated faster soccer-related reaction times. It seems that hope avoids feelings of discouragement and despair, both in training and in competition: if an athlete can preserve hope even after a disappointing performance "there is more likelihood that the full utilization of resources can be restored" (38, p. 247) .…”
Section: Discussionmentioning
confidence: 99%
“…Team sports constitute an appropriate environment to explore emotional responses, since those responses can play an important role in determining the groups' behavioural patterns (6) and may be significant for determining the success of groups (2) . Moreover, some authors referred that although emotions can be experienced in several competitive moments, researchers should consider the emotional states of athletes before the competition, since different negative emotions (e.g., anxiety) may negatively affect subsequent performance (48,63) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a new type of model is needed. A review of certain papers on emotions and sports/golf performance, makes it clear that 'performance was significantly greater in the anger condition compared with the happiness and emotion-neutral condition' [6]. Several pieces of evidence also support the claim that 'optimal emotional states would increase the probability of improved golf performance' [7].…”
Section: Proposed Alternative Modelmentioning
confidence: 99%